Miniature I-shaped Patch for Metal-mountable UHF RFID Tag Design - Ripin N.; Zamil N.; Ansari M.N.M.; Nordin N.A.; Aziz A.A.; Lim E.-H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Antenna grounds; Metals; Microstrip antennas; Mobile antennas; Slot antennas; Folded tag; High frequency radios; I-shaped antenna; Metal-mountable; Novel structures; Radiating patches; Radio-frequency-identification; Radiofrequency identification tags; T-slot; Ultra-high-frequency; Radio frequency identification (RFID)